Surrendering to utopia : an anthropology of human rights - Goodale, Mark. (Stanford, Calif. : Stanford University Press, 2009)
Surrendering to Utopia is a critical and wide-ranging study of anthropology's contributions to human rights. Providing a unique window into the underlying political and intellectual currents that have shaped human rights in the postwar period, this ambitious work opens up new opportunities for research, analysis, and political action. At the book's core, the author describes a "well-tempered human rights"--An orientation to human rights in the twenty-first century that is shaped by a sense of humility, an appreciation for the disorienting fact of multiplicity, and a willingness to make the mundaneness of social practice a source of ethical inspiration. In examining the curious history of anthropology's engagement with human rights, this book moves from more traditional anthropological topics within the broader human rights community - for example, relativism and the problem of culture - to consider a wider range of theoretical and empirical topics. Among others, it examines the link between anthropology and the emergence of "neoliberal" human rights, explores the claim that anthropology has played an important role in legitimizing these rights, and gauges whether or not this is evidence of anthropology's potential to transform human rights theory and practice more generally.
Introduction : a well-tempered human rights -- Becoming irrelevant : the curious history of anthropology and human rights -- Encountering relativism : the philosophy, politics, and power of a dilemma -- Culture on the half shell : universal rights through the back door -- Human rights along the grapevine : the ethnography of transnational norms -- Rights unbound : anthropology and the emergence of neoliberal human rights -- Conclusion : human rights in an anthropological key.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Human rights -- Anthropological aspects; Political anthropology; Electronic books; Anthropologie politique; Livres numériques.; e-books.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Human rights -- Anthropological aspects; Political anthropology; Menschenrecht; Politische Anthropologie; Human rights -- Anthropological aspects; Political anthropology; Human rights -- Anthropological aspects; Menschenrecht; Political anthropology; Politische Anthropologie